Biomechanical Characterization of Scallop Shells Exposed to Ocean Acidification and Warming - Abarca-Ortega, Aldo; Muñoz-Moya, Estefano; Pacheco Alarcón, Matías; García-Herrera, Claudio M.; Celentano, Diego J.; Lagos, Nelson A.; Lardies, Marco A. (Frontiers in Bioengineering and Biotechnology, 2022)
Increased carbon dioxide levels (CO2) in the atmosphere triggered a cascade of physical and chemical changes in the ocean surface. Marine organisms producing carbonate shells are regarded as vulnerable to these physical (warming), and chemical (acidification) changes occurring in the oceans. In the last decade, the aquaculture production of the bivalve scallop Argopecten purpuratus (AP) showed declined trends along the Chilean coast. These negative trends have been ascribed to ecophysiological and biomineralization constraints in shell carbonate production. This work experimentally characterizes the biomechanical response of AP scallop shells subjected to climate change scenarios (acidification and warming) via quasi-static tensile and bending tests. The experimental results indicate the adaptation of mechanical properties to hostile growth scenarios in terms of temperature and water acidification. In addition, the mechanical response of the AP subjected to control climate conditions was analyzed with finite element simulations including an anisotropic elastic constitutive model for a two-fold purpose: Firstly, to calibrate the material model parameters using the tensile test curves in two mutually perpendicular directions (representative of the mechanical behavior of the material). Secondly, to validate this characterization procedure in predicting the material’s behavior in two mechanical tests.